The emerging role of pyroptosis-related inflammasome pathway in atherosclerosis - Xiao-Dan Xu; Jia-Xian Chen; Lin Zhu; Shu-Ting Xu; Jian Jiang; Kun Ren (BMC, 2022)
Abstract Atherosclerosis (AS), a chronic sterile inflammatory disorder, is one of the leading causes of mortality worldwide. The dysfunction and unnatural death of plaque cells, including vascular endothelial cells (VEC), macrophages, and vascular smooth muscle cells (VSMC), are crucial factors in the progression of AS. Pyroptosis was described as a form of cell death at least two decades ago. It is featured by plasma membrane swelling and rupture, cell lysis, and consequent robust release of cytosolic contents and pro-inflammatory mediators, including interleukin-1β (IL-1β), IL-18, and high mobility group box 1 (HMGB1). Pyroptosis of plaque cells is commonly observed in the initiation and development of AS, and the levels of pyroptosis-related proteins are positively correlated with plaque instability, indicating the crucial contribution of pyroptosis to atherogenesis. Furthermore, studies have also identified some candidate anti-atherogenic agents targeting plaque cell pyroptosis. Herein, we summarize the research progress in understating (1) the discovery and definition of pyroptosis; (2) the characterization and molecular mechanisms of pyroptosis; (3) the regulatory mechanisms of pyroptosis in VEC, macrophage, and VSMC, as well as their potential role in AS progression, aimed at providing therapeutic targets for the prevention and treatment of AS.